Loaves and Fishes: Sustaining Anthropology at McGill - Trigger, Bruce G. (Culture, 1997)
The McGill anthropology department provides an example of a small and poorly funded department striving to achieve excellence by concentrating its limited resources on a few highly specific objectives. Initially the goal of the department was to study the impact of economic development on indigenous peoples. While this focus shaped early recruitment of teaching staff and the graduate program, other considerations, especially the needs of the undergraduate program, required a broader coverage of anthropology. In recent decades the shift from a behaviourist to a cognitive orientation in anthropology has encouraged increasing emphasis on cultural anthropology at the graduate level as social change and development have come to be viewed increasingly from a perceptual point of view. The dialectic between the needs of the graduate and the undergraduate programs has promoted a combination of focus and flexibility that in retrospect has served the department well.